The enlightenment from Malaysian consumers' perspective toward cosmetic products - Ain Ayob; Ammar Ihsan Awadh; Juliana Jafri; Shazia Jamshed; Hawa Mas Azmar Ahmad; Hazrina Hadi (Wolters Kluwer Medknow Publications, 2016)
Backgrounds: Variety of cosmetic products was used in our daily life, yet the amount and types of the cosmetic products used by the consumers were varied, which may be due to the different perspectives held by each of the consumers. Objectives: To explore consumers' perspectives toward cosmetic products. Methods: An interview guide was developed with a set of 12 semistructured questions. Participants in Kuantan, Pahang were recruited via the purposive sampling, and they undergo in-depth face-to-face interviews. All of the interviews were audio-recorded, transcribed verbatim, and were analyzed via thematic content analysis. Results: For the awareness of cosmetic products, less aware about the cosmetic products in Malaysia were noted among the participants. In terms of perceptions about the cosmetic products, participants expressed positive perceptions toward natural cosmetic products, quality were seen as synonymous with branded products and halal certification. Next, for the attitude toward the use of cosmetic products, participants were influenced by ingredients, product brand, and halal certification. Based on personal experiences, they provide complaints and suggestions for the enhancement of cosmetic products' quality. Conclusions: Participants were found to have less awareness about the cosmetic products in Malaysia. Besides, they realized about the chemical ingredients and halal certification for the cosmetic products. Therefore, they held positive perceptions and practiced positive attitudes toward natural and halal cosmetic products. Finally, adverse reactions from the use of cosmetic products were commonly experienced by the participants, which contributed mainly by the ingredients. Thus, they hoped for serious approached to be enacted to solve this problem.